Colistin enhances caspofungin antifungal efficacy against Aspergillus fumigatus by modulating calcium homeostasis and stress responses - Laura Cristina García Carnero; Xingyue Li; Patrícia Alves de Castro; Camila Figueiredo Pinzan; Jonatas Erick Maimoni Campanella; Iran Malavazi; Mami Yoshimura; Luis Alberto Vega Isuhuaylas; Yoko Yashiroda; Charles Boone; Nir Osherov; Sara Fallah; et al. (Nature Communications)
Abstract Fungal infections cause more than 2.5 million deaths a year. Due to emerging antifungal drug resistance, novel strategies are urgently needed to combat life-threatening fungal diseases. Here, by screening a collection of 5297 compounds derived from three chemical libraries, we demonstrate that the antibacterial agent colistin (COL) can potentiate the fungistatic echinocandins caspofungin (CAS) and anidulafungin, as well as the structurally distinct cell wall targeting antifungal ibrexafungerp against Aspergillus fumigatus. Chemical and genetic screenings revealed that protein kinase C and the transcription factor SltA are involved in the mechanism of action of COL. SltA is essential for coping with calcium-limiting conditions, and the addition of calcium rescues COL-susceptibility. COL + CAS decreases A. fumigatus infection in human pulmonary cells, Galleria mellonella, and Caenorhabditis elegans. In summary, we demonstrate that the mechanism of COL as a synergizer of CAS against A. fumigatus is the disruption of the cell membrane permeability and calcium homeostasis.